The Effect of Information Asymmetry, Financial Performance, Financial Leverage, Managerial Ownership on Earnings Management with the Audit Committee as Moderation Variables - Evodila Evodila; Erlina Erlina; Azizul Kholis (Institute of Computer Science (IOCS), 2020)
Earnings management is a very interesting topic to discuss. As long as management prepares financial reports in accordance with accounting standards in Indonesia, it cannot be said to do earnings management. However, on the other hand accrual-based accounting can cause distortion. This study aims to analyze the effect of information asymmetry, financial performance, financial leverage and managerial ownership as factors that affect earnings management in companies implementing Initial Public Offering (IPO) policies for the 2014-2018 period. This study will also test the audit committee variable which is used as a moderating variable in the research model. The population is companies that carry out Initial Public Offering (IPO) policies for the 2014-2018 period. The population of this study was 149,?5%, information asymmetry and managerial ownership have a significant effect on earnings management, while financial performance and financial leverage do not have a significant effect on earnings management. The results of this study also indicate that the audit committee is able to moderate the effect of information asymmetry on earnings management, on the other hand, the audit committee is unable to moderate financial performance and financial leverage on earnings management.